Efficient CsPbBr3 Perovskite Light‐Emitting Diodes Enabled by Synergetic Morphology Control. Issue 4 (27th December 2018) - Cheng, Li‐Peng; Huang, Jing‐Sheng; Shen, Yang; Li, Guo‐Peng; Liu, Xiao‐Ke; Li, Wei; Wang, Yu‐Han; Li, Yan‐Qing; Jiang, Yang; Gao, Feng; Lee, Chun‐Sing; Tang, Jian‐Xin
Abstract: The development of solution‐processed inorganic metal halide perovskite light‐emitting diodes (PeLEDs) is currently hindered by low emission efficiency due to morphological defects and severe non‐radiative recombination in all‐inorganic perovskite emitters. Herein, bright PeLEDs are demonstrated by synergetic morphology control over cesium lead bromide (CsPbBr3 ) perovskite films with the combination of two additives. The phenethylammonium bromide additive enables the formation of mixed‐dimensional CsPbBr3 perovskites featuring the reduced grain size (<15 nm) and efficient energy funneling, while the dielectric polyethyleneglycol additive promotes the formation of highly compact and pinhole‐free perovskite films with defect passivation at grain boundaries. Consequently, green PeLEDs achieve a current efficiency of 37.14 cd A −1 and an external quantum efficiency of 13.14% with the maximum brightness up to 45 990 cd m −2 and high color purity. Furthermore, this method can be effectively extended to realize flexible PeLEDs on plastic substrates with a high efficiency of 31.0 cd A −1 . Abstract : Bright all‐inorganic CsPbBr3 perovskite light‐emitting diodes are enabled by synergetic morphology control with the combination of two additives, leading to the formation of highly compact and pinhole‐free mixed‐dimensional perovskite films with small grains and defect passivation. The high external quantum efficiency of 13.14% is obtained with high brightness and color purity.